Parental Practice and Problem Video Game Playing in Adolescents - - Romdzati; Nilawan Chanthapreeda (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2013)
The descriptive design study was conducted to describe demographic data, parental practice, and problem video game playing in adolescents. Data was collected from 224 parents and 224 adolescents who study in one primary, one secondary, and one high school in Yogyakarta municipality, Yogyakarta province, Republic of Indonesia. It was collected using parental practice in video game playing adolescents’ questionnaires and problem video game playing (PVP) scale during April to May 2013. The results showed that the majority of parents were in good practice level. Parental practice in video game playing in adolescents was at a moderate practice (18.8%, n=42) and good practice (81.2%, n=182). There were no parents in bad practice level. The majority of adolescents were non problematic playing. There were 84.4 % (n=189) non problematic playing, while 15.6% (n=35) were problematic playing.